Sod Harvesting Intervals of Four Warm-Season Turfgrasses for Halosulfuron and Sulfentrazone. (March 2014) - McCullough, Patrick E.; De Barreda, Diego Gómez; Reed, Thomas V.; Yu, Jialin; Waltz, F. Clint
Abstract : Sedges are problematic weeds that reduce quality of turfgrass sod, and herbicides may be needed for control prior to harvesting. The objective of this research was to evaluate application timing of halosulfuron and sulfentrazone on sod quality, tensile strength, and postharvest rooting of four warm-season turfgrasses. Bermudagrass injury from herbicides was minimal (< 10%), but injury to centipedegrass, St. Augustinegrass, and zoysiagrass was detected before harvesting and generally increased with sulfentrazone rate from 0.21 to 0.84 kg ai ha −1 . Sod tensile strength was not reduced from the nontreated for bermudagrass and centipedegrass treated with herbicides, but tensile strength was reduced 15 and 22% following herbicide applications 1 wk before harvesting (WBH) St. Augustinegrass and zoysiagrass, respectively. Sulfentrazone at 0.84 kg ha −1 reduced zoysiagrass tensile strength 20% from the nontreated, but other treatments did not reduce measurements. Turfgrass injury from halosulfuron was negligible on all species, and treatments did not affect sod tensile strength of the four species. Treatments did not affect root mass of any species at 4 wk after sod transplanting. Sod quality after transplanting was reduced from the nontreated on several dates for centipedegrass and St. Augustinegrass when treated with sulfentrazone 1 and 2 WBH, and zoysiagrass quality was reduced from treatments 4 WBH. Bermudagrass quality after transplanting was not reduced from the nontreated by any herbicides. Results suggest sod harvesting should be delayed 1, > 2, > 2, and ≥ 4 weeks after sulfentrazone applications at labeled rates for bermudagrass, centipedegrass, St. Augustinegrass, and zoysiagrass, respectively. Sod harvesting should be delayed 1, 2, ≥ 4, and 2 wk after halosulfuron treatments at 0.07 kg ai ha −1 for bermudagrass, centipedegrass, St. Augustinegrass, and zoysiagrass, respectively.